Analysis of Khayyam's quatrains based on Plachik's emotional theory - Alireza Nabiloo; Fereshteh Dadkhah (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
In recent decades, interdisciplinary studies in literary research have made literary research new and attractive. Considering the capacity of the quatrain as one of the forms of Persian poetry and emotion which are one of the main components of the poem, in this research, Khayyam’s quatrains have been studied and analyzed from a psychological perspective. The theoretical framework of this article is Plutchik’s theory. According to this theory, eight emotions are common to all living things. These eight emotions include Destruction, Joy, Incorporation, Orientation, Protection, Deprivation, Rejection, and Exploration. All the emotional dimensions of Plutchik can be deduced in Khayyam’s quatrains. The dimensions of Destruction were 37 items, Joy 90 items, Incorporation 107 items, Orientation 61 items, Protection 32 items, Deprivation 130 items, Rejection 43 items, and Exploration 103 items. Although the prevailing view is that the core of Khayyam’s intellectual system focuses on happiness and debauch, this psychological study reveals that in these quatrains, anguish dominates happiness and joy. The results of this study reveal a part of the dimensions of Khayyam’s emotional personality.